Cut-off measurement of waist circumference for the diagnosis of abdominal obesity in a population of Erbil City, Iraq // Medida de corte de la circunferencia de la cintura para el diagnóstico de obesidad abdominal de una población en la ciudad de Erbil, Irak - Muhammad Ahmed, Sangar; Ismail, Sherzad A. (Investigación Clínica, 2020)
Abstract Waist circumference has been commonly used as a simple and clinically useful representative marker for central adiposity. The aim of this study was to investigate the optimal cut-off measurement of waist circumference of an Erbil population for diagnosing abdominal obesity. A cross sectional study was conducted in Erbil city. A total of 800 adult men and women (≥18year) of 800 different families were selected using a stratified multistage probability random sampling. Central obesity was defined according to the International Diabetes Federation criteria. Data was analyzed by using the statistical package for the social science, version 22. Receiver Operating Characteristic curves is designed to determine the cut-off point for waist circumference for both genders. A p value ≤ 0.05 was regarded as statistically significant. The cut-off value for male using the Receiver Operating Characteristic ROC curve was 94.7cm (sensitivity 82%, specificity 32%).The cut-off vale for female using the ROC curve was 97cm (sensitivity 55%, specificity 67%). We report a high prevalence of metabolic syndrome and abdominal obesity, especially in women, among the Erbil population. We recommend that these WC cut-off values be integrated into local preventive policies for public health, as the local criteria for diagnosing abdominal obesity, metabolic syndrome and related diseases. Resumen La circunferencia de la cintura se ha usado comúnmente como un marcador representativo simple y clínicamente útil para la adiposidad central. El objetivo de este estudio fue investigar la medida de corte óptima de la circunferencia de la cintura de la población de Erbil para diagnosticar la obesidad abdominal. Se realizó un estudio transversal en la ciudad de Erbil. Un total de 800 hombres y mujeres adultos (≥18 años) de 800 familias diferentes se seleccionaron mediante un muestreo aleatorio estratificado de múltiples etapas de probabilidad. La obesidad central se definió de acuerdo con los criterios de la Federación Internacional de Diabetes. Los datos se analizaron utilizando el paquete estadístico para las ciencias sociales, versión 22. Las curvas de características operativas del receptor están diseñadas para determinar el punto de corte para la circunferencia de la cintura para ambos sexos. Un valor de p ≤ 0,05 fue considerado como estadísticamente significativo. El valor de corte para hombres que utilizan la curva ROC de características de funcionamiento del receptor fue de 94,7 cm (sensibilidad del 82%, especificidad del 32%). El valor de corte para mujeres que utilizan la curva ROC fue de 97 cm (sensibilidad del 55%, especificidad del 67%). Se reporta una alta prevalencia de síndrome metabólico y obesidad abdominal, especialmente en mujeres, entre la población de Erbil. Recomendamos que estos valores de corte de WC se integren en las políticas preventivas locales para la salud pública como los criterios locales para diagnosticar la obesidad abdominal, el síndrome metabólico y las enfermedades relacionadas.